THE CONSTRUCTION OF THE LORENZ CURVE AND ESTIMATION OF INDICATORS OF DIFFERENTIATION OF MONETARY INCOMES OF POPULATION BASED ON EXPONENTIAL DISTRIBUTION - V. Lebedev; K. Lebedev (Вестник университета)
The article discusses the use of the two-parameter exponential distribution function to construct the Lorenz curve and to calculate such indicators of differentiation of population by income, as the Gini coeficient, Rainbow coeficient, Funds coeficient etc. It is shown that all these coeficients depend on the ratio of two parameters: the minimum and the average per capita monetary incomes of the population. For a quantitative estimation of the parameters of the distribution function numerical methods of solving the problem of minimization of different criteria of the proximity of theoretical curve and statistical data were used.